PENGARUH LIKUIDITAS, RISIKO KREDIT DAN KECUKUPAN MODAL TERHADAP PROFITABILITAS PERBANKAN DI INDONESIA - B2091161011, REGINA SELASMARCE KURNIATI (MAKSI UNTAN, 2020)
This study aims to determine the effect of liquidity, credit risk and capital adequacy on profitability in banks in Indonesia. This study also aims to find out the differences in the effect of liquidity, credit risk and capital adequacy on profitability between private bank companies and state bank companies. The independent variables in this study are LAR, LDR, NPL and CAR. The number of samples in this study are 120 variable samples. The results of this study indicate that the variable LAR, LDR and CAR do not have a significant effect on ROA, NPL variables have a significant effect on ROA on the LAR variable has no difference to the profitability between private bank companies and state bank companies while the LDR, NPL and CAR variables have different effects on profitability between private bank company and a state bank company.Keywords: liquidity, credit risk, profitability, loan to asset ratio, loan to deposit ratio, capital adequacy ratio.DAFTAR PUSTAKABursa Efek Indonesia, Laporan Keuangan Tahunan 2014, 2015, 2016 dan 2017. www.idx.co.idDominique. 2015. Pengertian Kredit Macet dan Penjelasannya di http://dominique122.blogspot.co.id/2015/05/pengertian-kredit-macet-dan.htmlÂ Ilmu, Titik Bening. 2016. Teori Likuiditas di https://berembunilmu.blogspot.co.id/2016/10/teori-likuiditas.htmlÂ Lestari, Dian. 2014. â€œPerbandingan Indikator Keuangan Antara Bank Umum Milik Negara Dengan Bank Umum Swasta Nasional di Indonesia. Journal Of Economic and Development, 92-105.Retna Atika Sari . 2017. â€œPengaruh Risiko Kredit, Risiko Likuiditas, dan Permodalan terhadap Profitabilitas Perbankan (Studi Kasus pada Bank Umum Go Public yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2015)â€. Skripsi. Univesitas Muhammadiyah Surakarta.Â Sahriani. 2015. â€œPengaruh Risiko Kredit dan Rasio Kecukupan Modal Terhadap Tingkat Profitabilitas pada Perusahaan yang Terdaftar di Bursa Efek Indonesiaâ€. Skripsi. Universitas Islam Negeri (UIN) Alauddin Makasar.Â Subramanyam dan John J. Wild. 2010. Analisis Laporan Keuangan. Buku Dua. Jakarta: Salemba EmpatWidyago. 2011. Manajemen Likuiditas Bank di https://widyago.wordpress.com/2011/03/27/manajemen-likuiditas-bank/